Pengaruh PAD, Dana Perimbangan dan Bantuan Keuangan Khusus (BKK) Terhadap Belanja Modal dan Kesejahteraan Masyarakat - Kirana, Sagung Ayu Indira Chandra; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 8, No. 6, Juni 2019, pp (1181-1442), 2019)
This research was conducted in nine districts / cities in Bali Province, using secondary data from 2013-2017 using path analysis / Path Anlisys techniques. The results of the analysis show that 1) regional original income and Special Financial Assistance (BKK) have a direct and significant effect on capital expenditure while the balancing fund has no significant effect on capital expenditure, 2) local revenue, balance funds, Special Financial Assistance (BKK) and expenditure capital has a significant effect on community welfare, 3) regional original income and Special Financial Assistance (BKK) have an effect on public welfare through capital expenditure, while capital expenditure does not mediate the effect of balancing funds on people's welfare. Keywords: PAD, balance funds, capital expenditure